واقع ممارسة مهنة التدقيق الخارجي بالجزائر على ضوء المعايير الجزائرية للتدقيق NAA -دراسة حالة عينة من المهنيين باستخدام برنامج MAXQDA-: The reality of practicing the external auditing profession in Algeria in the light of the Algerian standards of auditing (NAA) -Case study of a sample of professionals using MAXQDA program - - برياطي حسين,; غالم نادية,; تدلاوتي يامنة, (Journal of North African Economies, 2025)
This study aims to address the reality of external auditing practice in Algeria in the light of the Algerian standards for auditing (NAA), relying on a qualitative approach represented in conducting semi-directedinterviews with a sample of Algerian statutory auditors. The content of the interviews was analysed using the MAXQDA2022 program. The study dealt with three main axes: the nature of external auditing, Algeria's experience in adopting international standards on auditing and finally the case study. The results of the study found a relative application of Algerian standards for auditing by the statutory auditors, as the reference was not fully issued until 2023.